Kedudukan dan Peran KPK dalam Penanganan Kasus Korupsi Penyerobotan Lahan Negara untuk Kelapa Sawit di Riau oleh Grup Duta Palma - Dilya Qory Nailuvar; Grace Deborah Lubis; Nafisa Azahra; Raden Roro Naura Aisyah Putri Prasetyo (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Corruption in the seizure of state land for oil palm in Riau is one of the biggest corruption cases in Indonesia. This case cost the state up to Rp78 trillion and involved many parties, including government officials, businessmen, and the public. The KPK has an important position and role in handling corruption cases of state land grabbing for oil palm in Riau. The handling of corruption cases of the seizure of state land for oil palm in Riau by the KPK is an important step in efforts to eradicate corruption in Indonesia. The handling of this case has shown that the KPK has a strong commitment in eradicating corruption. However, there are still several things that need to be done to improve the effectiveness of handling corruption cases of state land grabbing for oil palm in Riau.